(untitled) (Iranian Journal of Kidney Diseases, 2015)
Abstract: After renal transplantation approximately forty percent of patients with Membranous Glomerolunephritis (MGN) had a recurrence, most commonly during the first year.We present two cases with recurrent MGN after kidney transplantation who successfully treated with Ritoximab.